Scientific production on martial arts and combat sports content in school physical education: a review study - Pereira, M. P. V. C.; Folle, A.; Milan, F. J.; Trusz, R.; Farias, G. O. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Background. There are few theoretical and practical tools for teaching martial arts and combat sports, such as teaching strategies, reports on successful or unsuccessful teaching experiences, pedagogical approaches that prioritize martial arts and combat sports, and systematic reviews. Problem and aim. This study aimed to systematically review the scientific literature on martial arts and combat sports in the con- text of school Physical Education. Methods. The review was conducted according to the Enhancing Transparency in Reporting the Synthesis of Qualitative Research (ENTREQ) protocol and the search form. The databases ERIC, LILACS, ProQuest, SCIELO, and SCOPUS were searched. They contained studies that discuss combat sports in school Physical Education. Results. A total of 8,038 articles were obtained from the initial search of databases, after duplicates were excluded, 5,361 articles remained. Studies were screened for eligibility according to inclusion and exclusion criteria. Two researchers analyzed first the titles, selecting 328 studies, then the abstracts, selecting 42 studies, and finally the full text. Ten studies were included in the review. Conclusions. It can be concluded that there is a need for new studies related to the theme, considering the range of contributions that mar- tial arts and combat sports can present to the students in the school scene, as well as assisting in the pedagogical practice of the teacher.